Management of Sepsis Patients Due to Community-Acquired Pneumonia in the Intensive Care Unit - Ardiayuman , Ardiayuman; Budipratama, Dhany (CoinReads Media Prima, 2025)
Introduction: Sepsis, a life-threatening response to infection, remains a critical global health issue, often triggered by community-acquired pneumonia (CAP) in vulnerable populations such as the elderly. This condition frequently requires intensive care unit (ICU) admission, necessitating adherence to evidence-based guidelines like the 2021 Surviving Sepsis Campaign (SSC) and Infectious Diseases Society of America (IDSA) recommendations. This case report highlights the application of these protocols in managing a complex sepsis case, emphasizing the role of early intervention and multidisciplinary care in improving outcomes. Case Description: A 67-year-old male, Mr. U, presented with a 3-day history of dyspnea and 1-day history of altered consciousness. Initial assessment revealed respiratory distress (respiratory rate 32/min, oxygen saturation 88% on room air, Glasgow Coma Scale 10), with chest radiography confirming CAP. Laboratory results showed a lactate level of 4.2 mmol/L and leukocytosis (18,000/mm³), indicating sepsis. In the ICU, the patient received oxygen therapy, followed by intubation due to worsening respiratory failure. Blood cultures were obtained, and empirical antibiotics (meropenem) were initiated within 1 hour per SSC guidelines. Fluid resuscitation (30 mL/kg crystalloids) and norepinephrine were administered for persistent hypotension. Bronchoscopy revealed purulent secretions, aiding diagnosis and management. After 5 days of ventilatory support and adjusted antibiotics, the patient stabilized and was transferred to a general ward. Conclusion: This case illustrates successful sepsis management due to CAP using SSC 2021 and IDSA guidelines. The integration of early antibiotics, fluid resuscitation, vasopressors, ventilation, and bronchoscopy underscores the efficacy of a multidisciplinary approach. Timely intervention in the ICU significantly improved survival and recovery, highlighting the need for further research to optimize protocols for such critical cases.